Massive open online courses: a review of usage and evaluation. (2015) - Sinclair, Jane; Boyatt, Russell; Rocks, Claire; Joy, Mike
The massive open online course (MOOC) has seen a dramatic rise in prominence over the last five years and is heralded by some as disrupting existing pedagogy and practices within the education sector, while others are far more sceptical about the impact of MOOCs. Numerous courses are now being offered on a number of different platforms, with participant numbers for some individual courses reaching hundreds of thousands. Expectations are high for what these courses can achieve in terms of opening access, widening participation and cost saving. In this paper we conduct a literature review to examine what is known about MOOCs (both those following the original connectivist model and the more traditionally didactic variety) and what indications there are that they can live up to such expectations. We discuss concerns arising from the review and identify issues including lack of evidence, absence of pedagogy, lack of support and unrealistic expectations particularly on beginner learners.